Food Sensory Factors and Restaurant Images on Customer Satisfaction: A Comparison of Franchise and Local Fast-Food Restaurant - Ahmad Riduan Bahauddin; Ling, Sing Wei; Sylvester Mantihal (ASIAN SCHOLARS NETWORK, 2020)
This study was conducted to investigate the effect of food sensory and restaurant image on customer satisfaction between the international and local franchise fast-food restaurants. Also, to identify the relationship of food sensory and restaurant image towards customer satisfaction. 420 completed survey was obtained from respondent respondents from one international food franchise chain restaurant and two local food that producing and sell the similar main dish (fried chicken). The results showed that the score for food sensory and restaurant image was higher in local restaurant as compared to the franchise restaurant. There is significant difference between franchise and local restaurants restaurant image and customer satisfaction (p<0.05). Food sensory and restaurant image factors were found to have a significant relationship (positive) with customer satisfaction (p<0.05). This shows that these two factors can influence customer satisfaction in fast food restaurant. Service quality is the most influential factor towards customer satisfaction for international franchise restaurant while food sensory has strong positive correlation towards customer satisfaction of local restaurant. food sensory and restaurant image highly contributes to customer satisfaction. The results obtained from the consumer survey provided a useful insight into consumers' satisfaction. These results will be beneficial to restaurant and business owner in sustaining their businesses in the foodservice industry.